2022
DOI: 10.3390/jcm11061691
|View full text |Cite
|
Sign up to set email alerts
|

Application of Translaryngeal Ultrasound (TLUS) in Patients with Neck Surgery—A Single-Centre, Prospective Cohort Study on Technique Evaluation

Abstract: Purpose: The primary objective of this study was to assess the value of translaryngeal ultrasound (TLUS) in assessing vocal fold (VF) function in patients after thyroid, parathyroid and neck lymph node surgery. Methods: A total of 219 patients that underwent 230 surgical procedures were enrolled in this prospective study. The study was conducted from October 2020 to October 2021. Patients’ VFs were analysed independently with TLUS and laryngoscopy before and after the surgery. Various TLUS variables, such as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The diagnosis of vocal fold paralysis is based on the asymmetric abduction and adduction movements of the vocal folds [ 10 ]. A recent study [ 11 ] showed that the movement of vocal folds are best assessed during whispering the vowel “e”. If the vocal folds are not visible from a midline approach due to acute shape or calcification of the thyroid cartilage, each vocal fold can be assessed laterally to the cartilage [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The diagnosis of vocal fold paralysis is based on the asymmetric abduction and adduction movements of the vocal folds [ 10 ]. A recent study [ 11 ] showed that the movement of vocal folds are best assessed during whispering the vowel “e”. If the vocal folds are not visible from a midline approach due to acute shape or calcification of the thyroid cartilage, each vocal fold can be assessed laterally to the cartilage [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Dedecjus et al[ 13 ], by applying Doppler gate to real-time B scan of vocal folds, signals corresponding to tissue motion were observed in the vibratory area of vocal folds during phonation. In contrast, another author [ 11 ] considered Doppler wave pattern a not necessary component of the TLUSG evaluation, being unable to replace the observation of vocal folds movement during phonation and respiration. Recently, TLUSG has been proposed as a promising noninvasive tool for routine preoperative and postoperative vocal cord examination in thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations